2019
DOI: 10.1002/ijc.32132
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of adverse events in randomized trials assessing immune checkpoint inhibitors

Abstract: The advent of immune checkpoint‐inhibitors (CPI) has transformed treatment for several cancer types. This review was performed to assess the rate of adverse events (AEs) associated with the use of CPI, alone or in combinations. A review of AEs reporting quality was also performed. All publications of Randomized Clinical Trials (RCTs) assessing CPI published before December 2017 were included. To investigate the quality of AEs reporting, a set of items was defined based on the 2004 CONSORT harms extension state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
163
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(189 citation statements)
references
References 31 publications
7
163
1
3
Order By: Relevance
“…A systematic review of 35 clinical trials showed a different pattern of toxicity regarding frequency and specific organ involvement depending on the type of therapeutic scheme that was administered (i.e., PD‐1/L1 inhibitor monotherapy, CTLA‐4 monotherapy, immunotherapy combination therapies, or concomitant administration of immunotherapy and chemotherapy; Fig. ) . The current guidelines for management of irAEs, based largely on toxicities with CTLA‐4 and PD‐1/L1 monotherapies, will likely require revision as experience with combination therapies continues to accrue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review of 35 clinical trials showed a different pattern of toxicity regarding frequency and specific organ involvement depending on the type of therapeutic scheme that was administered (i.e., PD‐1/L1 inhibitor monotherapy, CTLA‐4 monotherapy, immunotherapy combination therapies, or concomitant administration of immunotherapy and chemotherapy; Fig. ) . The current guidelines for management of irAEs, based largely on toxicities with CTLA‐4 and PD‐1/L1 monotherapies, will likely require revision as experience with combination therapies continues to accrue.…”
Section: Introductionmentioning
confidence: 99%
“…Frequency of (A) any grade and (B) grade 3/4 adverse events in clinical trials of PD‐1/L1 inhibitors, CTLA‐4 inhibitors, immunotherapy combinations, and chemotherapy plus immunotherapy combinations . *, Myositis and mucositis not included because these adverse events were NA for all groups except for PD‐1/L1 inhibitor.…”
Section: Introductionmentioning
confidence: 99%
“…Anti‐CTLA‐4‐associated irAEs are generally more severe, and trend towards (entero‐)colitis and hypophysitis. Hyperthyroidism and pneumonitis are more common with anti‐PD‐1/PD‐L1 targeting , with pembrolizumab having been reported to frequently cause vitiligo, implying tolerance break and autoimmunity . Interestingly, the incidence of irAEs appears to increase with the administered dose of ipilimumab, but not anti‐PD‐1 agents .…”
Section: Toxicity Of Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…Several organ specific AE rates varied among tumor sites. The most frequent AEs of any grade with PD‐1/PD‐L1 inhibitors and CTLA‐4 inhibitors alone were diarrhea (11% and 36%), fatigue (21% and 25%) pruritus (15% and 25%) and rash (10% and 23%) . The frequency of colitis ranged from 8% to 22%.…”
Section: Toxicity Profilementioning
confidence: 99%
“…The most frequent AEs of any grade with PD-1/PD-L1 inhibitors and CTLA-4 inhibitors alone were diarrhea (11% and 36%), fatigue (21% and 25%) pruritus (15% and 25%) and rash (10% and 23%). 3 The frequency of colitis ranged from 8% to 22%. It was reported that hypophysitis can affect up to 10% of patients treated with anti-CTLA-4 inhibitors.…”
Section: Toxicity Profilementioning
confidence: 99%